(untitled) (Damascus University Journal of Historical Studies, 2023)
The form of royal deification is a phenomenon that can be considered exceptional in the history of ancient Mesopotamia, as it was associated with specific people and a specific period of time, through which kings sought to impart a kind of sanctity to further consolidate their rule and confirm their legitimacy. Despite all the manifestations of divinity that the kings surrounded themselves with, but in fact they remained far from the real deification, as they could not be immortalized except through their achievements and deeds, which were the best evidence of their survival in our memory after thousands of years. The research first deals with the first worships of prehistoric man, which included the elements of nature, natural phenomena and animals. The research then discusses the worship of ancestors, then the worship of the mother goddess, which refers to fertility and continuity, up to the historical ages and the emergence of many gods, followed by the emergence of the phenomenon of worshiping the king during the era of King Naram-Sin of Akkad and what preceded him in Mesopotamian mythology. The research will also cover the period of the Sumerian revival through the dynasties of Lagash and Ur III, and conclud with the era of the Isin and Larsa dynasties, with a discussion about the manifestations of this deification and its compatibility with the truth.